From the global to the everyday: Anti-globalization metaphors in Trump's and Salvini's political language - Katja Freistein; Frank Gadinger; Christine Unrau (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2020)
In this paper, we ask how exactly right-wing populists make anti-globalization appealing. We follow the growing interest in the ambivalent features of populist language and performances by suggesting a methodological framework around narratives, metaphors, and emotions. We argue that right-wing populists skillfully present abstract phenomena of globalization and translate them to individual experiences of 'ordinary people'. Metaphors play a crucial role in populist storytelling as they make sense of a complex reality through imagery. They mobilize collective emotions and reach a wider audience through a high degree of linguistic adaptability and normative ambiguity. We demonstrate these narrative operations using two recent cases of 'successful' right-wing populist, anti-globalization storytelling, which build on strong metaphors. One is the metaphor of the 'House', used by former Italian Deputy Prime Minister and Interior Minister Matteo Salvini, and the other is U.S. President Donald Trump's metaphor of 'The Wall'. We argue that these metaphors are used to create an inside/outside distinction that externalizes threats which are possibly internal (e.g. drug consumption) to a polity (e.g. external drug abuse or organized crime) but can be blamed on globalization through the use of metaphors. What is more, metaphors can be utilized to construct a crisis, which in turn makes it possible for populists to adopt the savior-role of an energetic hero, who alone is able to resolve the supposed crisis.
urn:nbn:de:hbz:464-20200407-121056-1
Keywords: 330; Metaphors; Populist Storytelling; Narrative Analysis; (Anti-)Globalization; Migration